In vitro Study of Ixora coccinea Fruit Extracts for their Antioxidant and Tyrosinase Inhibitory Activities - J A, Sindhu Rani (Asian Journal of Biological and Life Sciences)
Aim: The aim of the study is to investigate the antioxidant and antityrosinase properties of Ixora coccinea Linn. fruit extracts from various solvents. Materials and Methods: The antioxidant property of the extract was tested by using 2,2 Diphenyl-1-picryl hydrazyl (DPPH) radical scavenging assay, antityrosinase activity by mushroom tyrosinase inhibitory method, and phenol estimation by Folin- Ciocalteu method. Results: The qualitative phytochemical screening confirmed the presence of alkaloids, flavonoids, tannins, phenols, and glycosides, in the fruit extracts. In vitro, antioxidant analysis showed that the methanolic fruit extract has good free radical scavenging activity when compared with standard Ascorbic acid and also exhibited potent tyrosinase inhibition using Kojic acid as a standard tyrosinase inhibitor. Conclusion: The present study proved that the methanolic fruit extract of Ixora coccinea has significant antioxidant and skin-whitening properties, and can be used for making skin care formulations that are safe and cost effective.
Keywords: Antioxidant activity; DPPH radical scavenging; Inhibitory potency of tyrosinase; Ixora coccinea Fruits; Total phenols